2022
DOI: 10.1021/acs.organomet.2c00365
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Ir-Catalyzed α-Amidation of 2-Acylimidazoles: Mechanism and Insertion Selectivity

Abstract: The mechanism and reactivity of Ir-catalyzed α-amidation of 2-acylimidazoles have been investigated at the B3LYP-D3 level, with the emphasis on nitrene insertion selectivity. The calculation results show that the catalytic mechanism consists of iridacycle formation, CO2 release, nitrene insertion, and amido protonation processes. Thereinto, nitrene insertion is both rate- and selectivity-determining steps. The origin of the nitrene group favorably inserting into an Ir–Cα over Cγ–H bond was further unraveled. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In addition to the above experimental work, some theoretical studies on the mechanisms of chiral amine synthesis have also been reported [25–28] . Zheng and co‐workers [26] studied Ir catalyzed α‐amidation of 2‐acylimidazoles and demonstrated a significant effect of nitrene insertion. Sunoj et al [27] .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition to the above experimental work, some theoretical studies on the mechanisms of chiral amine synthesis have also been reported [25–28] . Zheng and co‐workers [26] studied Ir catalyzed α‐amidation of 2‐acylimidazoles and demonstrated a significant effect of nitrene insertion. Sunoj et al [27] .…”
Section: Introductionmentioning
confidence: 96%
“…[23,24] In addition to the above experimental work, some theoretical studies on the mechanisms of chiral amine synthesis have also been reported. [25][26][27][28] Zheng and co-workers [26] studied Ir catalyzed α-amidation of 2-acylimidazoles and demonstrated a significant effect of nitrene insertion. Sunoj et al [27] investigated the mechanistic insights into asymmetric amination of diazoacetate catalyzed by dirhodium tetra(trifluoro)acetate with chiral SPINOL-phosphoric acid and found a stereo-controlling transition state with cooperative participation of both catalysts.…”
Section: Introductionmentioning
confidence: 99%